PESTICIDAL PLANT SPECIES IMPACT ON WHIP SMUT REDUCTION AND SUGARCANE (SACCHARUM OFFICINARUM L.) PRODUCTION IN NIGERIA - Moses Samuel BASSEY; Emmanuel Abraham SHITTU; Shema Andrew MONDAY; Alawode Victor OLALEKAN; Ekaette Eunice ETIM; Ekaette Joy ETOPOBONG; Fadeiye EBENEZER (Journal of Plant Development)
Yield decline due to Whip smut is an issue that has plagued sugarcane production in Nigeria. The objective of the study was to evaluate the inhibitory effect of pesticidal plants at varying rates of application on whip smut disease for sugarcane genotypes production. Green house experiment was conducted in 2018 and 2019 at National Cereals Research Institute, Badeggi in the Southern Guinea Savanna ecology of Nigeria. The treatments consists of factorial combination of two sugarcane genotypes, B47419 and NCS 008, three plant extracts, (Moringa, Neem, Cassia) and three levels of application rates (40, 60, 80 g/l) arranged in a completely randomized design (CRD) replicated three times. The results showed that genotype B47419 suppressed Sporisorium scitamineum germination and penetration than NCS 008, and gave a higher growth and yield of sugarcane than NCS 008. Brix content was highest under B47419 than NCS 008. The application of Cassia plant extracts at the rate of 80 g suppressed Sporisorium scitamineum germination and penetration, produced higher growth and yield of sugarcane. In conclusion, application of Cassia plant extracts at 80 g was the best in managing Sporisorium scitamineum, effectively boast brix content and sustain the productivity of sugarcane in the study area and related ecologies.